Developing Global Competence in Heritage Speakers. Educational Challenges in Cultural Diversity in the United States - Lorena García-Barroso (El Guiniguada)
This article examines how education can effectively foster global competence in Spanish heritage speakers in the United States. Despite their multilingualism and multiculturalism, they face barriers within the educational system, where their linguistic skills are often undervalued compared to standardized academic Spanish. This marginalization impacts their linguistic self-esteem and limits their participation in formal educational settings. The study highlights the importance of key strategies to strengthen global competence, including more inclusive educational approaches, the use of translanguaging, specialized teacher training, and the incorporation of authentic materials in the classroom. These strategies help recognize and value linguistic diversity, promoting a more equitable education aligned with the multicultural realities of the 21st century.